2011
DOI: 10.1371/journal.pone.0025460
|View full text |Cite
|
Sign up to set email alerts
|

Historical Reconstruction Reveals Recovery in Hawaiian Coral Reefs

Abstract: Coral reef ecosystems are declining worldwide, yet regional differences in the trajectories, timing and extent of degradation highlight the need for in-depth regional case studies to understand the factors that contribute to either ecosystem sustainability or decline. We reconstructed social-ecological interactions in Hawaiian coral reef environments over 700 years using detailed datasets on ecological conditions, proximate anthropogenic stressor regimes and social change. Here we report previously undetected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 67 publications
1
73
0
Order By: Relevance
“…Global patterns of decline in coral reef SESs have been documented (Jackson et al 2001, but evidence of recovery and sustainable SES interactions are also emerging (Cinner et al 2009b, Kittinger et al 2011, Lotze et al 2011). The differences in trajectories of SESs highlight the need to understand the human dimensions associated with sustainability or decline.…”
Section: Introductionmentioning
confidence: 99%
“…Global patterns of decline in coral reef SESs have been documented (Jackson et al 2001, but evidence of recovery and sustainable SES interactions are also emerging (Cinner et al 2009b, Kittinger et al 2011, Lotze et al 2011). The differences in trajectories of SESs highlight the need to understand the human dimensions associated with sustainability or decline.…”
Section: Introductionmentioning
confidence: 99%
“…For example, organized fishing interests heckled crowds and decision makers at public meetings, filed petitions to delay an administrative decision, and lobbied new legislators in an attempt to block approval of rules. Respondents frequently reported that organized interests opposed any rules changes despite documented resource depletion across the Hawaiian archipelago (Friedlander and DeMartini 2002;Kittinger et al 2011;Nadon et al 2015). To overcome strategic costs, community members raised public awareness, lobbied legislators, and encouraged citizens to support their proposals.…”
Section: Strategic Costsmentioning
confidence: 99%
“…Despite the geographic isolation of the NWHI, anthropogenic influences are present (Selkoe et al 2008), though their magnitude is much less compared to the populated MHI. Over the past century, fishing effort in the N WHI, especially for reef fish, has been relatively low (Kittinger et al 2011), and fishing has been prohibited in the region since 2000. In contrast, fisheries in the MHI have been exploited since AD 1250 with increasing pressure commensurate with a growing population during the last century (Kittinger et al 2011).…”
Section: Study Regionmentioning
confidence: 99%
“…Over the past century, fishing effort in the N WHI, especially for reef fish, has been relatively low (Kittinger et al 2011), and fishing has been prohibited in the region since 2000. In contrast, fisheries in the MHI have been exploited since AD 1250 with increasing pressure commensurate with a growing population during the last century (Kittinger et al 2011). Coral reef fisheries in Hawaii exploit multiple species but especially herbivorous fishes such as parrotfishes and surgeon-fishes (Friedlander & Parrish 1997).…”
Section: Study Regionmentioning
confidence: 99%